Optimasi Fuzzy Times Series Untuk Memprediksi Besar Nilai Penjaminan Kredit KUR dengan Algoritme Genetika (Studi Kasus : Perum Jamkrindo Cabang Kendari) - Sri Wahyuni; Budi Darma Setiawan; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Every businessmen would want to expand his business to be bigger, to do that it needs a lot of funds. The bank can provide kredit usaha rakyat with some of reqruitment collateral that has be obeyed by bussinesmen, one of them is to provide guarantee, the problem is not all the bussinesment can provide the guarantor. Therefore bussnismen need guarantor institution help in order to fulfill the requiment. As the Demand from banks for credit guarantee to increase every month, it ensures that the guarantor institution must increase its budget to guarantee the kredit usaha rakyat. Therefore a system that is able to predict the amount of guarantee value will be needed in order to meet the demand of the bank. In this research the method used to predict is Fuzzy Time Series which will be optimized using Genetic Algorithm. A chromosome is used to represent the interval of a membership function. The reproduction method is one-cut-point crossover and uniform mutation. And do the selection process by using elitism selection. The optimal results obtained with the length of chromosome as much as 100, the population size of 350, cr and mr of 0.3 and 0.6 and the number of generations as much as 1000. The error and fitness value generated by 0.00901% for MAPE and 110.95098192994908 for fitness value.